2018
DOI: 10.1002/aelm.201800106
|View full text |Cite|
|
Sign up to set email alerts
|

Static and Dynamic Magnetic Properties of Single‐Crystalline Yttrium Iron Garnet Films Epitaxially Grown on Three Garnet Substrates

Abstract: sections. Yttrium iron garnet (YIG) is extensively used for SW devices [11][12][13] because of its low intrinsic Gilbert damping, [14][15][16][17][18][19] but other materials with low Gilbert damping have been proposed, including Permalloy [20,21] and Heusler alloys. [22] However, films of low anisotropy materials such as YIG and Permalloy are typically magnetized in plane due to the dominant shape anisotropy and require a substantial external outof-plane magnetic field to saturate the film. This motivates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The unit cell volume of this rhombohedral lattice was 1.9628 nm 3 (). These values were similar to those used in our previous studies 76 . X-ray reflectometry (XRR) measurements showed that the films had a smooth surface with an average roughness, R a , of 0.47 nm and exhibited a density, ρ , of 5.17 g cm −3 (see Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The unit cell volume of this rhombohedral lattice was 1.9628 nm 3 (). These values were similar to those used in our previous studies 76 . X-ray reflectometry (XRR) measurements showed that the films had a smooth surface with an average roughness, R a , of 0.47 nm and exhibited a density, ρ , of 5.17 g cm −3 (see Fig.…”
Section: Resultssupporting
confidence: 91%
“…The propagation of SWs in the film was characterized as described in a previous article 76 . Six pairs of antennas with various spacings were fabricated on the YIG film, and transmittance of signals between each pair of antennas was measured using a vector network analyzer (VNA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations on garnet interfaces have been confined to epitaxial garnet films on gadolinium gallium garnet (GGG). [ 14–16 ] Jakubisova et al attributed the anomaly in MO polar Kerr rotation in nm‐thick yttrium iron garnet (YIG) on GGG (111) to the presence of a transition layer with opposite Fe 3+ sublattice magnetization that is antiferromagnetically coupled to the dodecahedral Gd 3+ in the substrate. [ 17 ] In other research, the formation of a magnetically compensated layer from the interdiffusion of Fe from the film and Gd‐Ga from the substrate is suggested as a result of high temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The intense interest in nanometer-scale epitaxial films of yttrium iron garnet (Y 3 Fe 5 O 12 , YIG) is supported by potential applications in magnonic devices [1][2][3], exploiting the idea of data transfer via spin waves (SWs) [4]. Magnonic applications are based on nanostructures, where SW can propagate with reduced loss over distances up to millimeters.…”
Section: Introductionmentioning
confidence: 99%